Subtitling, Semiotics and Spirited Away - Sanders, Lisa (Journal of Audiovisual Translation, 2022)
When translating a film according to typical subtitling models, the focus is usually solely on the dialogue of the film. Furthermore, the resulting translations are often impoverished to a large extent due to the constraints of the medium. The combined effects of this result in a significant loss of equivalence between the subtitles and the original linguistic and extralinguistic information. A potential method of preventing this loss is the application of a semiotic model for translation during the subtitling process. To this end, an existing model for the semiotranslation of film was enhanced and applied to the subtitling of the wildly popular Japanese animated film Spirited Away (2001). The resulting subtitles were evaluated for equivalence with the source text (ST) against the existing subtitle track that was distributed on a DVD release of the film. It was found that much more information, both from dialogue and on-screen extralinguistic content, could be conveyed by the semiotic subtitles than those created following more traditional subtitling norms. Lay summary When subtitles are created for films, the translators usually focus only on the dialogue that is spoken. Subtitles also often tend to have missing information, and are not written word-by-word. This is due to the rules for subtitles regarding their length and how long they are allowed to remain on-screen. Because of the information that is left out, the translations can sometimes be inaccurate. Subtitles also often ignore other aspects of a film, such as symbolic details in the visuals as well as in the choice of certain words over others. In order to try to prevent the loss of these details, this article explores a way of translating films through examining and analysing the signs and symbols that are represented in the film, especially in the dialogue. This method was applied to the popular Japanese animated film Spirited Away (2001), and subtitles created according to it were compared with the subtitles that are available on a DVD of the film. The comparison shows that it is possible to explain more of the missing information by translating with a focus on the symbols used in the film instead of trying to rely only on a straightforward translation of the dialogue.